2015
DOI: 10.1017/s0007114515003517
|View full text |Cite
|
Sign up to set email alerts
|

Synergic hypocholesterolaemic effect ofn-3 PUFA and oestrogen by modulation of hepatic cholesterol metabolism in female rats

Abstract: n-3 PUFA such as EPA and DHA as well as oestrogen have been reported to decrease blood levels of cholesterol, but their underlying mechanism is unclear. The purpose of this study was to determine the effects of the combination of n-3 PUFA supplementation and oestrogen injection on hepatic cholesterol metabolism. Rats were fed a modified AIN-93G diet with 0, 1 or 2 % n-3 PUFA (EPA + DHA) relative to the total energy intake for 12 weeks. Rats were surgically ovariectomised at week 8, and, after 1-week recovery, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
(50 reference statements)
1
9
0
Order By: Relevance
“…In rodents, n ‐3 PUFA supplementation promotes decreased serum cholesterol and hepatic cholesterol content that has been associated or not with reduced HMG CoA reductase and SREBP‐2 expression . In our study, we observed that FO reduced serum cholesterol in the adolescent standard diet offspring (Fig.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…In rodents, n ‐3 PUFA supplementation promotes decreased serum cholesterol and hepatic cholesterol content that has been associated or not with reduced HMG CoA reductase and SREBP‐2 expression . In our study, we observed that FO reduced serum cholesterol in the adolescent standard diet offspring (Fig.…”
Section: Resultssupporting
confidence: 54%
“…F) observed in STD offspring that received FO. N ‐3 PUFAs are also able to increase cholesterol output into the bile and its conversion to bile acids . In adolescent FO‐treated STD offspring, we observed reduced free cholesterol content (Fig.…”
Section: Resultsmentioning
confidence: 66%
“…The decrease in cholesterol concentration may be explained by suppression of hepatic cholesterol synthesis and to enhance hepatic cholesterol breakdown. Dietary n-3 PUFAs has been reported to increase the hepatic bile acid synthesis by up-regulation and to decrease blood levels of cholesterol by down-regulation of specific enzymes in rats (Oh et al 2015). Probably, the lowering effect of higher n-3 PUFA content on serum cholesterol found in chickens fed LO diets could reflect this inhibition.…”
Section: Blood Serum Metabolitesmentioning
confidence: 98%
“…Indeed, such a protective role for estrogen has been previously reported, but remains controversial. [30][31][32][33] Interestingly, in the female population included in this study, the levels of cholesterol and TG increased with age, even beyond menopause. On the other hand, it is possible that estrogen contributes to the increased levels of TG.…”
Section: Discussionmentioning
confidence: 66%